Conference Record of the Thirty-Ninth Asilomar Conference onSignals, Systems and Computers, 2005.
DOI: 10.1109/acssc.2005.1599818
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Message Passing Schedules for LDPC Decoding

Abstract: Abstract-The major drawback of the LDPC codes versus the turbo-codes is their comparative low convergence speed: 25-30 iterations vs. 8-10 iterations for turbo-codes. Recently, Hocevar showed by simulations that the convergence rate of the LDPC decoder can be accelerated by exploiting a 'turbo-scheduling' applied on the bit-node messages (rows of the parity check matrix). In this paper, we show analytically that the convergence rate for this type of scheduling is about two times increased for most of the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 6 publications
2
41
0
Order By: Relevance
“…The layered belief propagation algorithm is a variation of the standard belief propagation [8], and achieves about two times faster decoding convergence due to the optimized scheduling of reliability messages [9]. The PCM can be viewed as a group of concatenated horizontal layers in which every layer represents the component code.…”
Section: Low Density Parity Check Codesmentioning
confidence: 99%
“…The layered belief propagation algorithm is a variation of the standard belief propagation [8], and achieves about two times faster decoding convergence due to the optimized scheduling of reliability messages [9]. The PCM can be viewed as a group of concatenated horizontal layers in which every layer represents the component code.…”
Section: Low Density Parity Check Codesmentioning
confidence: 99%
“…This algorithm is a variation of the standard belief propagation [4], and achieves about two times faster decoding convergence due to the optimized scheduling of reliability messages [11]. The PCM can be viewed as a group of concatenated horizontal layers as shown in Fig.…”
Section: Layered Belief Propagation Algorithmmentioning
confidence: 99%
“…Sequential scheduling was introduced as a sequence of checknode updates in [3] and [4] and as a sequence of variable-node updates in [5] and [6]. It is also presented in [7] under the name of Layered BP (LBP), in [8] and [9] as serial schedule, in [10] as row message passing, column message passing and row-column message passing, among others.…”
mentioning
confidence: 99%
“…Monte-Carlo simulations and theoretical analysis in [3]- [10] show that sequential scheduling converges twice as fast as flooding when used in LDPC decoding. It has also been shown that sequential updating doesn't increase the decoding complexity per iteration, thus allowing the convergence speed increase at no cost [10], [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation